How Much does the Exam Cost for People? The Essay about the Corruption in Higher Education - ТитаевКирилл Дмитриевич (Journal of Economic Sociology, 2010)
The first part of the paper is devoted to the description of the embeddedness of the corruption mechanisms into the system of higher education. The second part is built on the quantitative data (survey in Irkutsk) and is focused on the scales of the corruption interactions in the contemporary higher education.